Awareness, knowledge and treatment decisions for erosive tooth wear: A case‐based questionnaire among Danish dentists. Issue 1 (30th October 2020) - Mortensen, Diana; Mulic, Aida; Pallesen, Ulla; Twetman, Svante
Abstract: Objective: To examine the knowledge and experience of erosive tooth wear (ETW) among Danish dental practitioners and, based on two cases, explore their treatment decisions. Methods: We sent a validated questionnaire electronically to all active members of The Danish Dental Association and The Association of Public Health Dentists in Denmark. The questionnaire had two parts; the first focused on scoring, recordkeeping, knowledge and experience of ETW. The second part presented two patients with different severity of erosive lesions to explore the dentists preventive and restorative treatment decisions. Results: We received 442 answers from 4, 490 potentially eligible dentists in Denmark (response rate 9.8%). The majority (78%) was female and the median age was 44 years. Nearly all respondents (97%) registered ETW in the charts and 49% recorded "always" or "often" the patients' diet history, most commonly with aid of interviews. The respondents perceived the prevalence of ETW to be higher today than 10–15 years ago and male patients (15–25 years) appeared more affected than females. The majority (82%) thought that they usually found the probable cause of the condition with carbonated beverages being the most common factor. The treatment included dietary guidance, soft tooth brushing with non‐abrasive fluoride toothpaste, topical fluoride applications and direct composite restorations. Conclusion: The majority of Danish dentists taking part of this survey had adopted a minimally invasive approach for the management of erosive tooth wear in young adults. There was however room for improvements in diagnosis, scoring and case documentation.